IMPLEMENTASI SISTEM SELF ASSESMENT PAJAK PENGHASILAN PASAL 25 PADA PT SYNERGI RAVELINO TOURS & TRAVEL - Saraswati, Dwi; Rioni, Yunita Sari (Universitas Pembangunan Panca Budi, 2025)
The purpose of this study is to describe the calculation, deposit and reporting as well as the application of accounting for Income Tax Article 25 at PT. Synergi Ravelino Tours & Travel. The data used in this study are secondary data obtained through documentation and observation of financial statements for the data in 2017. The analytical method used in this study is descriptive analysis with a qualitative approach. The results of this study indicate that the calculations made by PT. Synergi Ravelino Tours & Travel complies with tax regulations. Delays in depositing and reporting Article 25 Income Tax will be subject to fines which can be detrimental to the company. The results of this study are PT. Synergi Ravelino Tours & Travel make deposits and report Article 25 Income Tax past the deadline set by the Taxation Law, thus subject to administrative sanctions.